Der Briefwechsel Richard Dedekind - Heinrich Weber - Scheel, Katrin (Abhandlungen der Akademie der Wissenschaften in Hamburg, 2014)
This volume provides the very first transcription of correspondence between Richard Dedekind and Heinrich Weber, one of the most important instances of written dialog between mathematicians in the 19th century. Nearly every subarea of mathematics is addressed in the letters, which intensively discuss nascent developments in the field. A register of persons and index of works ease access to the topics discussed in the letters.